Production of Protease Enzyme from Wheat Straw - Atiya, Mohammed A. (Al-Khwarizmi Engineering Journal, 2018)
Protease enzyme production was studied and optimized as  a first step to collect information about solid state fermenter) to produce protease enzyme. A local isolated Aspergillus niger was used for this study with constant spores feeding in every experiment at (105/g). Experiments carried out in conical flasks with (250 ml) containing (10 g) of wheat straw as a substrate with different conditions included temperature, pH, hydration ratio, and fermentation time, the results comprised by measuring protease activity (u). The results showed that the best activity can be obtained at (T = 32°C, t= 100 hrs, pH= 2.5 and hydration ratio is 1:3). On the other hand the results is courage to proceed to design a solid state protease fermenter from wheat straw.